2008
DOI: 10.1093/brain/awn318
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after spontaneous and arteriovenous malformation-related intracerebral haemorrhage: population-based studies

Abstract: Spontaneous (non-traumatic) intracerebral haemorrhage (ICH) has a high case-fatality and leaves many survivors disabled. Clinical characteristics and outcome seem to vary according to the cause of ICH, but population-based comparisons are scarce. We studied two prospective, population-based cohorts to determine differences in outcome [case-fatality and modified Rankin Scale (mRS)] after incident ICH due to brain arteriovenous malformations (AVM) [Scottish Intracranial Vascular Malformation Study (SIVMS), n = 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
83
1
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(96 citation statements)
references
References 23 publications
5
83
1
7
Order By: Relevance
“…21,22 Applying a 1% annual hemorrhage rate to our hypothetical patient aged 45 years, the lifetime risk of BAVM rupture decreases to 30%. If the chance of serious morbidity or mortality after a BAVM hemorrhage is in the range of 27% to 40%, 6,7 then the lifetime risk of death or significant clinical impairment would be approximately 10%. Therefore, to provide clinical benefit for patients with unruptured BAVM, if such low long-term hemorrhage rates are correct, the risk of BAVM treatment must be less than the natural history of these lesions to justify intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 Applying a 1% annual hemorrhage rate to our hypothetical patient aged 45 years, the lifetime risk of BAVM rupture decreases to 30%. If the chance of serious morbidity or mortality after a BAVM hemorrhage is in the range of 27% to 40%, 6,7 then the lifetime risk of death or significant clinical impairment would be approximately 10%. Therefore, to provide clinical benefit for patients with unruptured BAVM, if such low long-term hemorrhage rates are correct, the risk of BAVM treatment must be less than the natural history of these lesions to justify intervention.…”
Section: Discussionmentioning
confidence: 99%
“…5 Second, the morbidity associated with arteriovenous malformations (AVM) bleeding may be less than previously thought. 6,7 Third, the risk of neurological injury after treatment of unruptured BAVM may be greater than previously described. [8][9][10] A randomized trial of unruptured brain arteriovenous malformations (ARUBA) was designed to compare the risk of observation versus prophylactic intervention for patients diagnosed with unruptured BAVM.…”
mentioning
confidence: 96%
“…Based on previous literature, prognosis of ICH related to arteriovenous malformation was known to be better 24 and that of anticoagulationrelated ICH worse than with other ICH. 14 -16 The ICH score developed by Hemphill and coworkers has been validated and used to evaluate the outcome of patients with ICH.…”
Section: Meretoja Et Al Smash-u: An Etiologic Classification Of Ich 2595mentioning
confidence: 99%
“…In 2009, van Beijnum et al reported a 40% rate of death or dependence in their population-based cohort 12 months after AVM-related intracerebral hemorrhage (ICH). 28 A more optimistic report from Hartmann et al found a 16% rate of at least moderately disabling deficit and no death after incident AVM hemorrhage in 115 patients. 29 From their review of the literature, Bendok et al assessed the risk of death after an AVM-associated hemorrhage to be from 10% to 15% while overall morbidity and mortality was estimated to be 15% per episode of hemorrhage.…”
Section: Epidemiology and Natural Historymentioning
confidence: 97%